TRIM58 suppresses the tumor growth in gastric cancer by inactivation of β-catenin signaling via ubiquitination - Liu, Xiaowen (Cancer Biol Ther, 2019)
Objective: To investigate and define the underlying molecular mechanism of tripartite motif-containing 58 (TRIM58) in regulating the tumor growth of gastric cancer (GC). Methods: TRIM58 expression in GC tissues and cells was detected by real-time PCR and Western blot, followed by lentiviral-induced overexpression or knockdown of TRIM58. Subsequently, CCK8, BrdU-ELISA, flow cytometry, immunoprecipitation, in vitro animal experiments and immunochemistry were performed to explore the function of TRIM58. Western blotting was used to detect β-catenin, C-myc, Cyclin D1, and survivin expression. Results: TRIM58 expression was significantly reduced in tumor tissues of GC patients and GC cell lines, whereas β-catenin, C-myc, Cyclin D1, and survivin were highly expressed. Overexpression of TRIM58 in GC cells resulted in decreases in β-catenin, C-myc, Cyclin D1, and survivin protein expression and significantly suppressed proliferation by preventing cell-cycle progression and promoting cell apoptosis. Conversely, TRIM58 knockdown resulted in the opposite effects. Furthermore, the effect of TRIM58 knockdown on GC cells was potently reversed by a β-catenin inhibitor, XAV939. Immunoprecipitations showed the interaction between TRIM58 and β-catenin, and TRIM58 overexpression significantly enhanced β-catenin degradation. In addition, we found a significant decrease in the growth and weight of tumors and an increase in tumor cell apoptosis in TRIM58-overexpression nude mice, which were also accompanied by reduced β-catenin expression. Conclusions: These data suggest that TRIM58 may function as a tumor suppressor in GC and potentially suppress the tumor growth of gastric cancer by inactivation of β-catenin signaling via ubiquitination.